Mechanical properties of Alumina - Ysz composite and 6061 Al Alloy joints fabricated by friction welding method - Uday, M. B.; Ahmad Fauzi, Mohd Noor; Zuhailawati, Hussain; Ahmad Badri, Ismail (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.